Environmental Sustainability in Higher Education: Mapping the Field - Luis Francisco Miranda; Jorge Oswaldo Sánchez Buitrago; Javier de Jesús Viloria Escobar (Revista Electrónica de Investigación Educativa)
A considerable amount of literature has been published on environmental sustainability in the context of higher education. However, no previous studies have investigated how environmental sustainability has evolved in the university context and little is known about the specific research trends in this field. In that sense, the main purpose of this study is to identify the most influential topics in university environmental sustainability research and the relationships between them. To that end, we conducted a keyword co-occurrence analysis of scientific articles published between 1989 and 2019. We were able to identify 23 core keywords. We then designed a map of associations between the terms, representing the relationships between them in thematic clusters. We found at least three major areas supporting environmental sustainability research in universities: environmental education, environmental sustainability integration, and environmental protection. Each research area is analyzed and discussed.